Brain signatures of error awareness during cognitive tasks for humans in the flight environment - Zhang, Peng; Yan, Juan; Liu, Zhongqi; Zhou, Qianxiang (Frontiers in Neuroscience, 2022)
At present, many scientific experiments are carried out in extreme conditions. Pilots need to perform high-intensity tasks for a long time. Human error is an essential factor affecting mission execution. To deeply study the physiological characteristics of different erroneous states of consciousness, we used an improved double-choice Oddball paradigm to collect brain electrophysiological signals of volunteers and pilots in missions and analyze event-related potential, time-frequency, and brain function spectrum, extracting EEG indicators sensitive to error awareness. The results showed that, in the 300~500ms time window, the error awareness type was correlated with Pe amplitude. Meanwhile, the time-frequency and brain functional spectrum analysis showed that the amplitude of the aware errors α-ERS oscillation, the functional spectral density of the α-band, and the uncertain errors was more prominent than unaware errors. The error awareness of the pilots showed the same EEG sensitivity characteristics in flight as in the ground volunteer experiment, and the characteristic sensitivity value was higher than that of the ground participants. We analyzed the EEG indicators sensitive to error awareness and determined the differences in EEG characteristics when pilots have error awareness on the ground and in flight. This study provides theoretical guidance for the follow-up research on the intervention measures against error awareness and determines the target point positioning.